THE EXISTENCE OF WOMEN’S LANGUAGE FEATURES IN MEN AND WOMEN INTERACTION IN THE ELLEN SHOW - Yohana Dian Rahayu Ningsih (ELTR Journal, 2018)
Well… has been considered as a linguistic hedging device and classified as “women’s language”. There are some phrases that are considered as “women’s language” but they are performed by men. This paper aims to investigate and examine the occurrences of women’s language feature in man and woman’s conversation in The Ellen Show. The data were gathered from the talk show video on YouTube uploaded by TheEllenShow Channel and the title of the video is “Snoop Dogg on Staying at Martha Stewart’s House and Teaching Ellen a New Word”. They were then collected, analyzed and categorized according to the features they show in the video. Findings indicate that women’s language features are performed not only by the woman but also by the man. The women’s language features that are performed by the man are mainly the lexical hedges. Meanwhile, the others that are performed by woman are the lexical hedges, tag question, intensifiers, and emphatic stress. This study hopes that the findings will give new insights about the woman’s language features existed in oral production or conversation between men and woman.